Possibilities to support elite adolescent athletes in improving performance: Results from a qualitative content analysis - Diehl, K.; Thielmann, I.; Thiel, A.; Mayer, J.; Zipfel, S.; Schneider, S. (Science & Sports, 2014)
Objectives: In their everyday life, elite adolescent athletes are faced with many challenges which can influence their performance. Therefore, the aim of our study was to ask young elite athletes what could possibly be done to support them in performing their sports and thus identify fields of improvement in elite adolescent sports. Equipment and methods: Data were drawn from the nationwide GOAL Study (German Young Olympic Athletes` Lifestyle and Health Study) on elite athletes aged between 14 and 18 years. Overall, 413 athletes answered the open-ended question ("In your opinion, what could be improved in order to facilitate performing your sport?"). The answers were analysed using qualitative content analysis. Results: The school setting was one of the most frequently cited problems according to elite adolescent athletes. They also stated that the way they were treated by their coaches, the financial support (not) offered to them, the - in their opinion - insufficient medical care, the distance to and the equipment of sport facilities, as well as the timing and structure of their training sessions needed reconsidering. By taking into account co-occurrences and gender differences of these identified categories, it was possible to reveal potential starting points for intervention aiming at improving elite adolescent athletes` performance. Therefore, the results are not only important for the athletes themselves but also for sport associations and coaches.